2006
DOI: 10.1111/j.1556-4029.2006.00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Likelihood Ratios in Fingerprint Identification for Configurations of Any Number of Minutiæ

Abstract: Recent court challenges have highlighted the need for statistical research on fingerprint identification. This paper proposes a model for computing likelihood ratios (LRs) to assess the evidential value of comparisons with any number of minutiae. The model considers minutiae type, direction and relative spatial relationships. It expands on previous work on three minutiae by adopting a spatial modeling using radial triangulation and a probabilistic distortion model for assessing the numerator of the LR. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 7 publications
0
84
2
Order By: Relevance
“…Further research, exploiting the abundance of optional statistical methods, may choose likelihood ratios [61], say, for improved quantification.…”
Section: Fingerprint Individuality and Quantifying Weight Of Evidencementioning
confidence: 99%
“…Further research, exploiting the abundance of optional statistical methods, may choose likelihood ratios [61], say, for improved quantification.…”
Section: Fingerprint Individuality and Quantifying Weight Of Evidencementioning
confidence: 99%
“…While LR D , which has a constant number of parameters, is simple to compute, there is a severe loss of information in going from probabilities of points in 2n-dimensional space to probabilities of a scalar value. However, due to its simplicity, the distance method is been widely used in fingerprint identification, 4 speaker verification, pharmaceutical tablet comparison, 8 etc.…”
Section: Distance Approximationmentioning
confidence: 99%
“…4,7 The distance-based approach assumes that k = [k 1 , .., k n ], and q = [q 1 , .., q n ] are points in a fixed-dimensional vector-space and that there exists a scalar distance D(k, q) between them. A likelihood ratio is defined as follows The number of parameters needed to characterize the probability distributions in Eq.…”
Section: Distance Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…These models have been based on very heterogeneous, and generally very small, samples and very disparate approaches (studying different types of minutiae, different fingerprint patterns, different fingers and different finger areas) see [17,18]. Recently, Neumann et al [22][23][24] and Egli et al [25] reported on the use of likelihood ratios as a means of objectively assessing the evidential weight of corresponding minutiae between a fingermark and a fingerprint.…”
Section: Introductionmentioning
confidence: 99%